Note on the Early Use of Aqua Vitae in Scotland - Scott-Moncrieff, Robert (Proceedings of the Society of Antiquaries of Scotland, 1916)
The article considers when whisky or its lineal ancestor became a common drink in Scotland. There is evidence to suggest that a grain distilled spirit of some sort was in fairly common use in the northern part of Europe by the end of the fifteenth century, and in Ireland by the beginning of the sixteenth century. However there is no evidence to support the belief that that such a spirit might also have been in common use in Scotland by 1500 although documentary references do appear in the Exchequer Rolls for 1494-95 to a malt distilled liquor. The term whisky appears to originate in the later sixteenth century.